2021
DOI: 10.4067/s0717-95022021000200401
|View full text |Cite
|
Sign up to set email alerts
|

Rendimiento Académico de Estudiantes Universitarios en Asignaturas de las Ciencias Morfológicas: Uso de Aprendizajes Activos Basados en Problemas (ABP)

Abstract: ORTEGA-CORTEZ, A.; ESPINOZA-NAVARRO, O.; ORTEGA, A. & BRITO-HERNÁNDEZ, L. Rendimiento académico de estudiantes universitarios en asignaturas de las ciencias morfológicas: Uso de aprendizajes activos basados en problemas (abp).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Teaching methodology that promotes active learning combined with ICT (information and communication technology) in which student participation is predominant is being implemented in university education with good results [ 4 , 5 , 6 , 7 ]. Within this active methodology, gamification plays a prominent role.…”
Section: Introductionmentioning
confidence: 99%
“…Teaching methodology that promotes active learning combined with ICT (information and communication technology) in which student participation is predominant is being implemented in university education with good results [ 4 , 5 , 6 , 7 ]. Within this active methodology, gamification plays a prominent role.…”
Section: Introductionmentioning
confidence: 99%
“…In Argentina, a study conducted on university students found that 30% of students did not efficiently complete their first years of study, mainly due to underperformance in the field of mathematics. Therefore, these results highlight the importance of addressing and improving student academic performance, especially in key areas such as mathematics, to promote greater student retention and success in higher education (Ortega et al, 2021). Likewise, Meza et al (2019) demonstrated that universities continue to employ the traditional teaching model, which consists of the teacher being the sole provider of knowledge and information, without allowing the student to develop.…”
Section: Introductionmentioning
confidence: 99%
“…Así como los autores citados, varios estudiosos han citado la idea del ABP como una estrategia didáctica que contribuye a la construcción del conocimiento a partir de una situación problemática y de manera autónoma. Al respecto, Ortega et al (2021) agregan lo siguiente: Uno de los cambios más connotados en la Educación actual es el uso de Tecnologías de Innovación de la Información y la Comunicación (TIC). Una de estas tecnologías es el Aprendizaje Basado en Problemas (ABP), cuya metodología de enseñanza se basa en el desarrollo de competencias y habilidades cognoscitivas y de integración entre los miembros de equipos de trabajo en el aula.…”
Section: Introductionunclassified